Molecular Docking and Pharmacokinetics Analysis of Phytochemicals from Piper caninum as Dengue NS2B-NS3 Protease Inhibitors: Evaluation of Phytochemicals as Inhibitor for NS2B-NS3 - Mustafa, Nur Farhana; Cheng, Kian Kai; Razali, Siti Aisyah; Nadri, Muhammad Helmi (Journal of Tropical Life Science, 2024)
Dengue fever affects 390 million people each year. Currently, there is no specific medicine to treat this disease. Thus, the search for potential NS2B-NS3 protease inhibitors has attracted increasing research interest. The dengue protease NS2B-NS3 was used as a molecular target because of its vital function in viral replication. Piper caninum belongs to the Piperaceae family, found inhabited in Malaysia and Indonesia. This plant possesses various phytochemicals with various health benefits. However, the anti-dengue activity of this plant is yet to be discovered. Therefore, the objective of this research is to evaluate the inhibitory activity of phytochemicals from P. caninum against NS2B-NS3 using in silico experimentation. Molecular docking using AutoDock Vina was utilized to identify the binding interaction of phytochemicals on NS2B-NS3. SwissADME and ProTox-II web servers were used to analyse the ADMET (absorption, distribution, metabolism, excretion, and toxicity) of the phytochemicals. Results showed that cepharadione A, bornyl caffeate, and (+)-bornyl p-coumarate had comparable molecular interaction with the reference compound, curcumin. Analysis of in silico pharmacokinetics properties revealed that these phytochemicals have good pharmacokinetics profiles and excellent drug-ability, which obeyed Lipinski’s Rule of Five. This study shows the potential inhibitory activity of the phytochemicals against NS2B-NS3 for a lead in the development of dengue inhibitors.